Enhancing Elementary Students’ Interaction and Cognitive Outcomes through ClassPoint-Integrated PowerPoint in Science Learning - Sutiani, Sutiani; Handhika, Jeffry; Listiani, Ivayuni (AL-ISHLAH: Jurnal Pendidikan, 2026)
Interactive digital media are increasingly used in elementary science learning, yet limited studies have measured learning interaction as a multidimensional construct in the use of real-time presentation tools. This study developed and evaluated ClassPoint-based interactive PowerPoint learning media to improve learning interaction and cognitive outcomes on Earth’s rotation and revolution among sixth-grade students.A Research and Development design was employed using the ADDIE model. The study involved eighteen sixth-grade students at SDN Sumber, Ngawi Regency, East Java, Indonesia. Data were collected through observation, questionnaires, interviews, documentation, and pre-test–post-test assessments. The instruments were validated by experts and tested for reliability. The data were analyzed using appropriate non-parametric statistical procedures.The developed media received strong expert validation and demonstrated high instrument reliability. After implementation, students showed significant improvements in learning interaction and cognitive learning outcomes. The interaction construct covered verbal participation, behavioral engagement, emotional involvement, and peer collaboration, enabling a comprehensive assessment of classroom engagement during the learning process.The findings indicate that ClassPoint-based interactive PowerPoint media can support student-centered elementary science learning by promoting active participation and strengthening conceptual understanding. The study contributes to technology-enhanced primary education by integrating real-time interactive presentation features with a measurable multidimensional interaction framework. These results offer practical implications for teachers seeking to design engaging, interactive, and conceptually meaningful science instruction in elementary classrooms.